2016
DOI: 10.1016/j.watres.2016.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoate synthesis by mixed microbial consortia cultured on fermented dairy manure: Effect of aeration on process rates/yields and the associated microbial ecology

Abstract: Polyhydroxyalkanoates (PHAs) are biodegradable polymers that can substitute for petroleum-based plastics in a variety of applications. One avenue to commercial PHA production involves coupling waste-based synthesis with the use of mixed microbial consortia (MMC). In this regard, production requires maximizing the enrichment of a MMC capable of feast-famine PHA synthesis, with the metabolic response induced through imposition of aerobic-dynamic feeding (ADF) conditions. However, the concept of PHA production in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…The 16S rRNA gene sequencing data showed the occurrence of different putative PHA-accumulating bacteria mainly represented by members of Gammaproteobacteria, Alphaproteobacteria and Bacteroidetes. This finding is in line with previous studies that have indicated the occurrence of functional redundancy in microbial consortia inhabiting PHAproducing systems (Coats et al, 2016;Huang et al, 2018;Inoue et al, 2016). This peculiarity may imply that the eventual species loss can be compensated by other microorganisms contributing similarly to functioning and to the stability of the biological process if perturbations or drastic changes occur.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 16S rRNA gene sequencing data showed the occurrence of different putative PHA-accumulating bacteria mainly represented by members of Gammaproteobacteria, Alphaproteobacteria and Bacteroidetes. This finding is in line with previous studies that have indicated the occurrence of functional redundancy in microbial consortia inhabiting PHAproducing systems (Coats et al, 2016;Huang et al, 2018;Inoue et al, 2016). This peculiarity may imply that the eventual species loss can be compensated by other microorganisms contributing similarly to functioning and to the stability of the biological process if perturbations or drastic changes occur.…”
Section: Discussionsupporting
confidence: 92%
“…Nowadays, the information about PHA-accumulating MMC in pilotscale systems is lacking and derives almost entirely from the application of cultivation-dependent and in situ hybridization techniques (Queirós et al, 2015). Recently, the application of 16S rRNA gene highthroughput sequencing has revealed the occurrence of high biodiversity along with functional redundancy in PHA-accumulating MMC (Coats et al, 2016;Huang et al, 2018). In this study, the concomitant use of in situ detection assays and sequencing techniques was applied in order to investigate microbial community composition and phaC genes diversity during the SBR operation.…”
Section: Discussionmentioning
confidence: 99%
“…However, with increasing scale the required power consumption for mixing and aeration becomes significant [79], and so the bioreactor operation parameters must be carefully managed in order to save aeration costs. This aspect is emphasized in PHA production/waste treatment operations using enriched mixed cultures [80].…”
Section: Engineering Significance: Effects On Oxygen Transfer Ratementioning
confidence: 99%
“…Industry focused on two polyesters: polylactic acid (PLA) and PHAs, where PLA is economical and available in bulk but PHAs are expensive. However, the applications and properties of PHAs can be tailored by varying the co-monomer and the content of the copolyesters [ 26 , 27 , 28 , 29 ]. The advantages and disadvantages of both PLA and PHAs are compiled in Table 1 .…”
Section: Sources Of Phasmentioning
confidence: 99%